Fístula gastroesplénica por adenocarcinoma gástrico y peritonitis difusa - Terry Castellano, Luis E. (2021)
The first case in Peru of a gastro-splenic fistula (GSF) secondary to gastric adenocarcinoma penetrating the splenic hilum, causing malignant splenic infarction and diffuse peritonitis, is reported. The rationale for surgical treatment is discussed. An 84-year-old man with diffuse peritonitis secondary to a Borrmann III (BIII) gastric adenocarcinoma fistulized to the spleen and in communication with the peritoneal cavity. Four cases of GSF associated with gastric cancer were found in the literature. The gastrectomy with curative intention in a single stage, would be indicated for cases with good general condition and criteria of curability. A second stage gastrectomy is reserved for cases with poor general condition and curability criteria. Local or palliative resections would be indicated for cases with poor general condition and incurability.